Formation and evolution mechanisms of topological and chemical short-range order in NiCoCr multi-principal element alloy during solidification process - Kefan Li; Zhaoyang Hou; Pengfei Zou; Jubo Wu; Quanhua Gao; Gang Shi; Sha Sha; Kejun Dong (Journal of Materials Research and Technology)
The nucleation mechanism of NiCoCr multi-principal element alloys (MPEAs) is investigated using molecular dynamics (MD) simulations. The cluster type index method (CTIM) was used to identify and characterize the topological structures of atomic cluster during the solidification process. The results reveal that, although thousands of atomic cluster types emerge during the solidification process, only 22-top cluster types play a critical role in nucleation. Three critical temperature points - T1 (1440 K), T2 (1418 K), and T3 (1390 K), respectively corresponding to the saturation points for ICO-like atomic clusters, BCC-like atomic clusters, defective HCP atomic clusters, appear in the nucleation and growth process. The microstructure of critical nucleus is affected by the cooling rate. Additionally, local chemical short-range order (CSRO) in NiCoCr MPEA is very weak in the high-temperature liquid and the high temperature solidified solid just below liquid-solid transformation, while there is not any CSRO in the low temperature solidified solid. This phenomenon is attributed to the competition between rapid cooling and atomic diffusion during the solidification process.